2014
DOI: 10.1016/j.cbpc.2014.06.005
|View full text |Cite
|
Sign up to set email alerts
|

The effects on steroidogenesis and histopathology of adult male Japanese quails (Coturnix coturnix japonica) testis following pre-pubertal exposure to di(n-butyl) phthalate (DBP)

Abstract: Keywords:Di-(n-butyl) phthalate Leydig cell Steroidogenesis Male Japanese quails Endocrine disruptionIn the present study, we have investigated the effects of 30-day dietary (pre-pubertal) exposure to different doses (0 (control), 1, 10, 50, 200 and 400 mg/kg bodyweight/day) of di(n-butyl) phthalate (DBP) on Leydig cells of adult male Japanese quails by quantifying the transcript levels for P450 side-chain cleavage (p450scc), P450c17 (CYP17), and 3β-and 17β-hydroxysteroid dehydrogenase (hsd) using quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 90 publications
3
23
0
1
Order By: Relevance
“…In rodents, most studies tend to expose the animals to greater or equal to 500 mg/kg, which is considered a high dose of phthalates, and effects on the male reproductive system development appear more pronouncedly. However, a few studies have showed some effects on the male reproductive system even with lower doses, such as 100 mg/kg [11,46,14,15,25,[47][48][49]. In this study, two DBP doses were tested (100 and 500 mg/kg), in order to observe the effect of this chemical on prostate development in rats.…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, most studies tend to expose the animals to greater or equal to 500 mg/kg, which is considered a high dose of phthalates, and effects on the male reproductive system development appear more pronouncedly. However, a few studies have showed some effects on the male reproductive system even with lower doses, such as 100 mg/kg [11,46,14,15,25,[47][48][49]. In this study, two DBP doses were tested (100 and 500 mg/kg), in order to observe the effect of this chemical on prostate development in rats.…”
Section: Discussionmentioning
confidence: 99%
“…This includes governmental support and stakeholder pressures. Innovation is achieved through financial incentives, financial resources or training program since, some authors address the importance of the external context of the company's competitive situation and its competition, as this context can influence the new investments and efforts necessary for a specific supply chain innovation [29]. However, as we a have discussed and shown in the previous study, improvement model development is follows the following approaches [27]:…”
Section: External Domainmentioning
confidence: 99%
“…DBP; Weir, Wooten, Smith & Salice 2014), that may affect thyroid function (Mathieu-Denoncourt et al, 2015), neurodevelopment, reduced steroidogenesis, genotoxic and antioxidant status effects (Qu, Feng, Sun & Wang 2014;Wang, Jiang, Ge, Chen, Yang, Ji, Zhong, Guan & Liu 2015), autism spectrum disorders, and development/ reproductive physiology in animals (Aoki, Harris, Katsiadaki & Sumpter 2011;Bello, Madekurozwa, Groenewald, Aire & Arukwe 2014;Bhatia, Kumar, Ogino, Gregg, Chapman, McLaughlin & Iguchi 2014;Chopra, Harley, Lahiff & Eskenazi 2014); furthermore, they are thought to be carcinogenic (Ahuactzin-Perez, Torres, Rodriguez-Pastrana, Soriano-Santos, Diaz-Godinez, Diaz, Tlecuitl-Beristain & Sanchez 2014). DBP; Weir, Wooten, Smith & Salice 2014), that may affect thyroid function (Mathieu-Denoncourt et al, 2015), neurodevelopment, reduced steroidogenesis, genotoxic and antioxidant status effects (Qu, Feng, Sun & Wang 2014;Wang, Jiang, Ge, Chen, Yang, Ji, Zhong, Guan & Liu 2015), autism spectrum disorders, and development/ reproductive physiology in animals (Aoki, Harris, Katsiadaki & Sumpter 2011;Bello, Madekurozwa, Groenewald, Aire & Arukwe 2014;Bhatia, Kumar, Ogino, Gregg, Chapman, McLaughlin & Iguchi 2014;Chopra, Harley, Lahiff & Eskenazi 2014); furthermore, they are thought to be carcinogenic (Ahuactzin-Perez, Torres, Rodriguez-Pastrana, Soriano-Santos, Diaz-Godinez, Diaz, Tlecuitl-Beristain & Sanchez 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Presently, DBP mode of action is unclear; independent studies have shown phthalates to be endocrine disruptors (4-6 carbon straight side chain compunds, i.e. DBP; Weir, Wooten, Smith & Salice 2014), that may affect thyroid function (Mathieu-Denoncourt et al, 2015), neurodevelopment, reduced steroidogenesis, genotoxic and antioxidant status effects (Qu, Feng, Sun & Wang 2014;Wang, Jiang, Ge, Chen, Yang, Ji, Zhong, Guan & Liu 2015), autism spectrum disorders, and development/ reproductive physiology in animals (Aoki, Harris, Katsiadaki & Sumpter 2011;Bello, Madekurozwa, Groenewald, Aire & Arukwe 2014;Bhatia, Kumar, Ogino, Gregg, Chapman, McLaughlin & Iguchi 2014;Chopra, Harley, Lahiff & Eskenazi 2014); furthermore, they are thought to be carcinogenic (Ahuactzin-Perez, Torres, Rodriguez-Pastrana, Soriano-Santos, Diaz-Godinez, Diaz, Tlecuitl-Beristain & Sanchez 2014). Antiandrogenic activity have been shown in adult male three-spined sticklebacks (Gasterosteus aculetaus) exposed to 15, and 35 mg DBP L À1 for 22 days by Aoki et al (2011); however it is unclear if they have any oestrogenic induction effect in fish (Ortiz-Zarragoitia, Trant & Cajaravillet 2006;Bhatia et al 2014;Chen, Li, Liu & Xu 2015).…”
Section: Introductionmentioning
confidence: 99%